Preparation method of high-stability manganese-based oxide potassium ion battery positive electrode material

The KMO@C0.2 potassium ion battery positive electrode material was prepared through solid phase reaction and high-energy ball milling process, which solved the problem of large particle size of the existing materials and insufficient K+ diffusion active sites, and achieved high capacity charging and discharge, excellent cycling stability and rate performance.

CN119683689AActive Publication Date: 2025-03-25GUIZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411849167.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The particle size of the existing potassium ion battery positive electrode material is large, resulting in insufficient K+ diffusion active sites, affecting electrolyte penetration and electrode polarization during electrochemical reactions, thereby limiting the battery's high-capacity charging and discharge performance.

Method used

The KMO@C0.2 potassium ion battery positive electrode material was prepared by solid phase reaction and high-energy ball milling. By mixing KMO with Kochen Black for high-energy ball milling, the KMO particles were smaller, the specific surface area was increased, and the surface was coated with a conductive amorphous carbon coating.

Benefits of technology

The high stability, excellent specific capacity, cycle life and rate performance of the positive electrode material of KMO@C0.2 potassium ion battery is achieved, reducing the polarization phenomenon of the electrode during the electrochemical reaction, and improving the high-capacity charging and discharge capability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683689A_ABST
    Figure CN119683689A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-stability manganese-based oxide potassium ion battery positive electrode material, which comprises the following steps: S1, taking 1.12 g of K2CO3 and 1.9275 g of MnO2 respectively, mixing and grinding the two medicines for 15 minutes; s2, loading the uniform powder obtained by grinding into a corundum crucible, then putting the corundum crucible into a muffle furnace, adjusting the heating rate to be 5 DEG C / min, heating to 700 DEG C, and keeping the temperature for 5 hours; according to the preparation method of the high-stability manganese-based oxide potassium ion battery positive electrode material provided by the invention, the prepared KMO and C0.2 potassium ion battery electrode has high stability, the KMO and C0.2 composite material has excellent specific capacity, cycle life and rate capability, the carbon coating can protect the surface of the KMO negative electrode for a long time and is not influenced by electrolyte side reaction, and the service life of the KMO negative electrode material is prolonged. Irreversible interface reaction and interface kinetics are reduced, the particle size is reduced by ball milling, and the specific surface area of the material and active sites of K + diffusion are increased, so that the specific capacity is greatly increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage devices and relates to a method for preparing a positive electrode material for a potassium ion battery, and specifically relates to a method for preparing a KMO@C0.2 positive electrode material for a potassium ion battery by solid phase reaction and high-energy ball milling. Background Art

[0002] The solid-state reaction route is to prepare layered manganese dioxide (δ-MnO 2 ) cathode, which is a simple method involving physical mixing (sometimes solution mixing) of potassium and transition metal precursors (oxides or acetates) and sintering to obtain the final product. For example, Kim [1] Using K 2 CO 3 and Mn 2 O 3 The precursors P3-K0.5MnO2 were synthesized via a conventional solid-state route. The stoichiometrically mixed powders were ground and then calcined at 800 °C for 12 h. The desired phase structure and crystallinity can be obtained by selecting appropriate precursors and controlling the calcination temperature. Liu [2] K was prepared by a simple solid phase method. 0.45 Mn 0.8 Fe 0.2 O 2 . The stoichiometric amount of K 2 CO 3 and Mn 2 O 3 and Fe 2 O 3 The powder was mixed with ethanol in air by wet planetary ball milling for 12 h. The pellets were calcined at 850 °C in air for 15 h to obtain K 0.45 Mn 0.8 Fe 0.2 O 2 This technology also uses a simple thermal sintering solution, and the raw material is also low-cost K 2 CO 3 and Mn 2 O 3 , but a two-step process is used, the second step is to convert K 0.28 MnO 2 · 0.29 H 2 O(KMO) and Ketjen black (KB) were prepared by high-energy ball milling to coat Ketjen black (a conductive carbon) on the surface of KMO to obtain KMO@C0.2 material.

[0003] Among various energy storage systems, lithium-ion batteries (LIBs) have become the main power source for consumer electronics and smart wearable devices due to their high energy density, long cycle life, and easy maintenance. However, LIBs alone may not be able to meet the future energy needs associated with the rapid growth of the electric vehicle market and stationary storage systems. Lithium is scarce and unevenly distributed in the earth's crust, which has raised concerns about the soaring lithium prices and the sustainability of lithium to meet future energy needs. Therefore, potassium-ion batteries (PIBs) are a promising alternative or supplement to lithium-ion batteries because potassium storage is abundant. It is well known that the cathode material is one of the keys to the excellent electrochemical performance of potassium-ion batteries. It can be roughly divided into organic compounds, layered transition metal oxides (LTMOs), Prussian blue analogs (PBAs), and polyanionic compounds (PACs). In particular, layered transition metal oxides (LTMOs) have attracted attention as one of the most promising cathodes in PIBs due to their high theoretical energy density, stable structure, and low cost.

[0004] Constructing a suitable coating matrix layer is an effective way to prevent the electrode from directly contacting the organic electrolyte. Inhibiting side reactions can improve interfacial stability and cycle stability. Surface coating effectively avoids direct contact between the positive electrode material and the electrolyte, inhibits the corrosion of the electrolyte on the positive electrode material and the dissolution of the transition metal, and is an effective surface modification method. An effective and direct strategy is to use a soft conductive matrix to buffer the volume change during potassium / depotassium. Carbon coating can improve the conductivity between particles and avoid direct contact between the electrolyte and the electrode, thereby improving rate performance and cycle stability. We adopted two strategies. First, we synthesized δ-MnO2 particles using a simple solid-state reaction route, which is a low-cost and high-yield synthesis method. Then the water molecules of deionized water are embedded in the interlayer of δ-MnO2 in the form of crystallized water to synthesize potassium birnessite (K-birnessite), named KMO. Secondly, a conductive amorphous carbon coating is coated on the KMO powder using a physical method through a high-energy ball milling process. The coating can not only provide a suitable conductive network to improve electronic conductivity, but also buffer the volume expansion of KMO particles and reduce agglomeration. Therefore, the KMO@C0.2 composite composed of flexible, conductive amorphous carbon and KMO particles is expected to exhibit excellent performance in PIBs.

[0005] Therefore, it is necessary to provide a method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material to solve the above technical problems. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing KMO@C0.2 potassium ion battery positive electrode material by solid phase reaction and high-energy ball milling. The potassium ion battery positive electrode material KMO@C0.2 prepared by the method has a smaller particle size than KMO, can increase the active sites for K+ diffusion, is beneficial to the penetration of electrolytes and reduces the polarization phenomenon of electrodes during electrochemical reactions, thereby enabling high-capacity charging and discharging of the battery.

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material, comprising the following steps:

[0008] S1. Get K 2 CO 3 、MnO 2 The masses of the two drugs were 1.12 g and 1.9275 g, respectively. The two drugs were mixed and ground for 15 min.

[0009] S2. Put the uniform powder obtained by grinding into a corundum crucible, and then put it into a muffle furnace, and adjust the heating rate to 5℃min -1 , rise to 700℃ and keep warm for 5h;

[0010] S3, wait for the muffle furnace to cool down to room temperature, use a circulating water vacuum pump to filter the black powder from the solid phase reaction with a large amount of deionized water to filter out the unreacted K 2 CO 3 And impurities such as potassium manganate;

[0011] S4. Put the washed powder into a vacuum drying oven at 80°C and dry for more than 8 hours to obtain the precursor material K of the first step process. 0.28 MnO 2 · 0.29 H 2 O(KMO);

[0012] S5, the second step is to use high-energy ball milling technology to mix a certain amount of KMO powder and Ketjen black (KB) powder, put them into a ball mill, and then put in agate balls with an appropriate ball-to-material ratio;

[0013] S6, setting the rotation speed and time of the planetary ball mill and ball milling KMO and KB to obtain the final product KMO@C0.2;

[0014] S7, KMO@C0.2, acetylene black, and polyvinylidene fluoride were mixed and dispersed in n-methyl-2-pyridone (NMP), mixed and ground to form a uniform slurry, and the obtained slurry was evenly coated on the surface of a clean aluminum foil treated with anhydrous ethanol, and dried in a vacuum oven at 80°C overnight to obtain a potassium ion battery positive electrode sheet.

[0015] S8, using a manual button cell slicer to punch out discs with a diameter of 14 mm, the effective mass loading of the cathode is about 1.0-2.0 mg cm-2 per electrode. Metallic potassium, 1M KPF6 (EC:DEC = 1:1 Vol%) and glass fiber were used as anode, electrolyte and separator, respectively. CR2032 coin cells were assembled in an argon-filled glove box, and the electrochemical performance of the prepared electrodes was evaluated.

[0016] Preferably, in step S1, the K 2 CO 3 、MnO 2 The molar ratio is 0.7:1, and 5wt% K 2 CO 3 , to make up for the potassium source lost under high temperature.

[0017] Preferably, the protective gas is any one or more of argon, nitrogen, helium and neon.

[0018] Preferably, in step S5, the mass of KMO is 0.8 g, and the mass of KB is 0.2 g.

[0019] Preferably, in step S7, the mass ratio of KMO@C0.2 to the conductive agent and the binder is 8:1:1.

[0020] Compared with the related art, the method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material provided by the present invention has the following beneficial effects:

[0021] (1) The KMO@C0.2 potassium ion battery electrode prepared by the present invention has high stability, and the KMO@C0.2 composite material has excellent specific capacity, cycle life and rate performance. The carbon coating can protect the KMO cathode surface for a long time, is not affected by electrolyte side reactions, and reduces irreversible interfacial reactions and interfacial dynamics. Ball milling reduces the particle size, increases the specific surface area of ​​the material and the active sites for K+ diffusion, thereby greatly increasing the specific capacity.

[0022] (2) The KMO@C0.2 potassium ion battery positive electrode prepared by the present invention has a discharge specific capacity of 137.9 mAh g-1 at a current density of 20 mAg-1, and has excellent energy storage properties.

[0023] (3) The KMO@C0.2 potassium ion battery positive electrode prepared by the present invention has excellent cycle performance, and the battery capacity retention rate is ≥81% in 300 cycles.

[0024] (4) The KMO@C0.2 potassium ion battery positive electrode prepared by the present invention has excellent rate performance. The discharge specific capacity of the KMO@C0.2 cathode is 137.9, 121.1, 110.6, 94.9, 77.2 and 59.8 mAh g-1, respectively. When the applied current density gradually increases from 20, 50, 100, 200, 500 and 1000 mA g-1, the reversible capacity of the KMO@C0.2 composite electrode gradually decreases with the increase of current density. When the current density is restored to 20 mA g-1, the specific capacity is restored to 110.3 mAh g-1, showing excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] like Figure 1 The figure shows a flow chart of the two-step process for preparing KMO@C0.2 as a potassium ion battery electrode in Example 1;

[0026] like Figure 2 Shown is a graph of the specific capacity of KMO@C0.2 prepared as a potassium ion battery electrode by a two-step process in Example 1;

[0027] like Figure 3 The figure shows the cycle performance of KMO@C0.2 prepared in Example 1 as a potassium ion battery electrode at a current density of 1000 mA / g;

[0028] like Figure 4 Shown is the rate performance diagram of KMO@C0.2 prepared in Example 1 as a potassium ion battery electrode.

[0029] Please refer to Figure 4, in which the preparation method of the high-stability manganese-based oxide potassium ion battery positive electrode material includes the following steps:

[0030] S1. Get K 2 CO 3 、MnO 2 The masses of the two drugs were 1.12 g and 1.9275 g, respectively. The two drugs were mixed and ground for 15 min.

[0031] S2. Put the uniform powder obtained by grinding into a corundum crucible, and then put it into a muffle furnace, and adjust the heating rate to 5℃min -1 , rise to 700℃ and keep warm for 5h;

[0032] S3, wait for the muffle furnace to cool down to room temperature, use a circulating water vacuum pump to filter the black powder from the solid phase reaction with a large amount of deionized water to filter out the unreacted K 2 CO 3 And impurities such as potassium manganate;

[0033] S4. Put the washed powder into a vacuum drying oven at 80°C and dry for more than 8 hours to obtain the precursor material K of the first step process. 0.28 MnO 2 · 0.29 H 2 O(KMO);

[0034] S5, the second step is to use high-energy ball milling technology to mix a certain amount of KMO powder and Ketjen black (KB) powder, put them into a ball mill, and then put in agate balls with an appropriate ball-to-material ratio;

[0035] S6, setting the rotation speed and time of the planetary ball mill and ball milling KMO and KB to obtain the final product KMO@C0.2;

[0036] S7, KMO@C0.2, acetylene black, and polyvinylidene fluoride were mixed and dispersed in n-methyl-2-pyridone (NMP), mixed and ground to form a uniform slurry, and the obtained slurry was evenly coated on the surface of a clean aluminum foil treated with anhydrous ethanol, and dried in a vacuum oven at 80°C overnight to obtain a potassium ion battery positive electrode sheet.

[0037] S8, using a manual button cell slicer to punch out discs with a diameter of 14 mm, the effective mass loading of the cathode is about 1.0-2.0 mg cm-2 per electrode. Metallic potassium, 1M KPF6 (EC:DEC = 1:1 Vol%) and glass fiber were used as anode, electrolyte and separator, respectively. CR2032 coin cells were assembled in an argon-filled glove box, and the electrochemical performance of the prepared electrodes was evaluated.

[0038] In step S1, the K 2 CO 3 、MnO 2 The molar ratio is 0.7:1, and 5wt% K 2 CO 3 , to make up for the potassium source lost under high temperature.

[0039] The protective gas is any one or more of argon, nitrogen, helium and neon.

[0040] In step S5, the mass of KMO is 0.8 g, and the mass of KB is 0.2 g.

[0041] In step S7, the mass ratio of the KMO@C0.2 to the conductive agent and the binder is 8:1:1.

[0042] This solution is low-cost and has a simple preparation process. First, the prepared KMO introduces crystal water compared to traditional δ-MnO2, which can enhance the cycle stability of the positive electrode material. This is a new development trend of manganese-based potassium ion positive electrode materials. Secondly, the modification method of the carbon coating has corresponding research progress in lithium-ion and sodium-ion batteries, but it is still a blank in potassium-ion batteries. The second step is the innovative use of high-energy ball milling technology to introduce the carbon coating technology into potassium-ion batteries. High-energy ball milling makes KMO particles smaller and increases the specific surface area, solving the problem of difficulty in increasing the capacity of potassium-ion batteries. The carbon coating avoids direct contact between the electrolyte and KMO. Compared with a single solid-phase reaction, it enhances the cycle stability and rate performance of the positive electrode material.

[0043] In this technical solution:

[0044] (1) The carbon coating material used is Ketjen black;

[0045] (2) The mass ratio of KMO to Ketjen black is 8:2;

[0046] (3) The speed of the planetary ball mill is 300 rpm, with forward rotation for 5 min, pause for 60 s, reverse rotation for 5 min, and pause for 60 s;

[0047] (4) The total ball milling time is 6 h;

[0048] (5) The mass ratio of large, medium and small natural agate balls is 1:1:1;

[0049] (6) The ball-to-material ratio is 20:1.

[0050] Through innovative material formula and preparation process, the electrochemical performance of the material is significantly improved, while the production cost is reduced. Its unique microstructure design not only optimizes the physical and chemical properties of the material, but also ensures that the finished product has excellent surface quality and shape stability, meeting the comprehensive requirements of high-end application fields for high performance, low cost and aesthetics of the material. The specific advantages are as follows:

[0051] (1) The KMO@C0.2 potassium ion battery electrode prepared by the present invention has high stability, and the KMO@C0.2 composite material has excellent specific capacity, cycle life and rate performance. The carbon coating can protect the KMO cathode surface for a long time, is not affected by electrolyte side reactions, and reduces irreversible interfacial reactions and interfacial dynamics. Ball milling reduces the particle size, increases the specific surface area of ​​the material and the active sites for K+ diffusion, thereby greatly increasing the specific capacity.

[0052] (2) The strong interfacial interaction between KMO@C0.2 particles and amorphous carbon through C=O bonds promotes the rapid charge transfer and improves the structural stability of the KMO@C0.2 composite electrode.

[0053] (3) The conductive carbon coating can not only provide a good conductive network and enhance the conductivity of electrons, but also buffer the volume expansion during the potassium addition / depotassium addition process and effectively reduce the agglomeration of KMO particles.

[0054] (4) The carbon coating prevents direct contact between MnO2 and the electrolyte, thus inhibiting the occurrence of side reactions.

[0055] (5) The two-step process still follows the original intention of low cost and high output, making it possible for cheap potassium-ion batteries to replace lithium-ion batteries in certain energy storage fields.

[0056] (6) The preparation method of manganese-based potassium ion batteries is no longer limited to transition metal element doping, two-step process and carbon coating, which enriches the modification methods of potassium ion positive electrode materials.

[0057] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material, characterized in that: The following steps are involved: S1. Take 1.12g and 1.9275g of K2CO3 and MnO2 respectively, mix and grind the two chemicals for 15 minutes; S2. Put the uniform powder obtained by grinding into a corundum crucible, and then put it into a muffle furnace, and adjust the heating rate to 5℃min -1 , rise to 700℃ and keep warm for 5h; S3, waiting for the muffle furnace to cool down to room temperature, using a circulating water vacuum pump to filter the black powder from the solid phase reaction with a large amount of deionized water to filter out impurities such as unreacted K2CO3 and potassium manganate; S4. Put the washed powder into a vacuum drying oven at 80°C and dry for more than 8 hours to obtain the precursor material K of the first step process. 0.28 MnO2 0.29 H2O; S5, the second step is to use high-energy ball milling technology to mix a certain amount of KMO powder and Ketjen black powder, put them into a ball mill, and then put in agate balls with an appropriate ball-to-material ratio; S6, setting the rotation speed and time of the planetary ball mill and ball milling KMO and KB to obtain the final product KMO@C0.2; S7, KMO@C0.2, acetylene black, and polyvinylidene fluoride were dispersed in n-methyl-2-pyridone (NMP), mixed and ground to form a uniform slurry, and the obtained slurry was evenly coated on the surface of a clean aluminum foil treated with anhydrous ethanol, and dried in a vacuum oven at 80°C overnight to obtain a potassium ion battery positive electrode sheet; S8. Use a manual button cell slicer to punch out discs with a diameter of 14 mm. The effective mass loading of the cathode is about 1.0-2.0 mg cm-2 per electrode. Use metallic potassium, 1M KPF6 (EC:DEC=1:1Vol%) and glass fiber as the anode, electrolyte and separator, respectively. Assemble CR2032 coin cells in an argon-filled glove box, and evaluate the electrochemical properties of the prepared electrodes.

2. The method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material according to claim 1, characterized in that: In step S1, the molar ratio of K2CO3 to MnO2 is 0.7:1, and 5 wt% of K2CO3 is added to compensate for the potassium source lost at high temperature.

3. The method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material according to claim 1, characterized in that: The protective gas is any one or more of argon, nitrogen, helium and neon.

4. The method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material according to claim 1, characterized in that: In step S5, the mass of KMO is 0.8 g, and the mass of KB is 0.2 g.

5. The method for preparing a high-stability manganese-based oxide potassium ion battery positive electrode material according to claim 4, characterized in that: In step S7, the mass ratio of the KMO@C0.2 to the conductive agent and the binder is 8:1:1.

Citation Information

Patent Citations

  • Preparation method and application of battery diaphragm

    CN116031571A

  • Hydrophobic organic coating modified sodium ion battery O3-phase layered oxide positive pole piece and preparation method and application thereof

    CN116682937A

  • Preparation and application of manganese-based positive electrode material based on electrochemical in-situ introduction of oxygen vacancy

    CN116768272A

  • Sheet-shaped positive electrode composite material for lithium ion secondary battery, manufacturing method thereof, and lithium ion secondary battery

    JP2020017437A

  • An Air Electrode for Lithium air battery using a composite of RuO2 / MnO2 / C and the manufacturing method thereof.

    KR1020160014939A